Revival and Development of Tunpu Villages within the Context of Rural Revitalization in China: The Contrasting Perspectives of Cultural Heritage and Tourism Industry - WU, Heng; LOO, Fung Chiat; CHAN, Cheong Jan (Journal of Environmental Management and Tourism, 2022)
The Tunpu (屯堡) village in Anshun city Guizhou province has unique cultural assets, particularly in the village’s spatial layout, its traditional building, and the spectacular Dixi (地戏) opera. In the context of the Chinese Rural Revitalization Strategy, a suitable combination of Cultural Heritage (CH) and the tourism industry to promote the rural revitalization of Tunpu Village is of practical significance. However, the Coronavirus disease (COVID-19) has had a severe impact on the rural revival of Tunpu Village. This article analyzes the current situation of rural revitalization in Tunpu villages from the perspectives of CH and the tourism industry through fieldwork of three Tunpu villages that have already developed tourism up to certain stages. We observed that the participation rate of villagers is not high; the villagers’ income through village tourism projects is generally low. While tourist attractions mainly consist of traditional architectural landscapes, buildings management and protection were an issue. CH plays an active role in the tourism industry, but the support provided to tourist facilities and entertainment projects could be further improved. The article concludes that the collaboration of the village government, villagers, and tourism company plays an essential role in integrating the tourism industry and CH. The right strategy is the guide, and the cooperation of the participants is the guarantee.